FULFILLMENT OF EDUCATION RIGHTS IN THE BORDER AREAS OF INDONESIA AND MALAYSIA - Endah Rantau Itasari (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2019)
The opening of access to education for all citizens is a conditio sine qua non value of freedom and justice. As long as there are citizens who cannot get access to education, even though at the most basic level, the state is the agency most responsible for this injustice. Without the guarantee of these basic needs, citizen participation in a democratic climate that allows for upward social movements to be far from expectations The elimination of discrimination should be done by providing the widest opportunity for every citizen to get an education, so that cheap schools, even free, will be created for all the people without exception. Therefore the government is required to be able to be fair by providing equal opportunities for every citizen to take education (formal) and be able to protect and guarantee the rights of citizens, especially for those who are financially incapable so that they can continue to receive proper education.